UPAYA MENINGKATKAN KETERAMPILAN PERENCANAAN KARIR MELALUI BIMBINGAN KELOMPOK METODE PROJECT BASED LEARNING PADA SISWA SMKN 2 KUDUS - Lilis Trisnawati; Edris Zamroni; Isyana Riya Umami (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The purpose of this study is to improve the career planning skills of students with low self-efficacy through group guidance using the Project Based Learning method. This research is an action study consisting of 2 cycles, with each cycle comprising 3 meetings. The researcher used career tree media in cycle 1 and a mind mapping in cycle 2. The results from the career planning scale showed a pre-test result of 45.73%. After the intervention, the students' ability to plan their careers increased by 29.79%, resulting in a career planning score of 75.52%. A further increase of 19.06% occurred from post-test 1 to post-test 2, bringing the percentage to 94.58%. Thus, it can be concluded that the Project Based Learning method through group guidance is effective in improving the career planning skills of students with low self-efficacy.